A Green Route for High-Yield Production of Tetramethylpyrazine From Non-Food Raw Materials - Li, Jing; Lu, Jian; Ma, Zhilin; Li, Jianxiu; Chen, Xianrui; Diao, Mengxue; Xie, Nengzhong (Frontiers in Bioengineering and Biotechnology, 2022)
2,3,5,6-Tetramethylpyrazine (TMP) is an active pharmaceutical ingredient originally isolated from Ligusticum wallichii for curing cardiovascular and cerebrovascular diseases and is widely used as a popular flavoring additive in the food industry. Hence, there is a great interest in developing new strategies to produce this high-value compound in an ecological and economical way. Herein, a cost-competitive combinational approach was proposed to accomplish green and high-efficiency production of TMP. First, microbial cell factories were constructed to produce acetoin (3-hydroxy-2-butanone, AC), an endogenous precursor of TMP, by introducing a biosynthesis pathway coupled with an intracellular NAD+ regeneration system to the wild-type Escherichia coli. To further improve the production of (R)-AC, the metabolic pathways of by-products were impaired or blocked stepwise by gene manipulation, resulting in 40.84 g/L (R)-AC with a high optical purity of 99.42% in shake flasks. Thereafter, an optimal strain designated GXASR11 was used to convert the hydrolysates of inexpensive feedstocks into (R)-AC and achieved a titer of 86.04 g/L within 48 h in a 5-L fermenter under optimized fermentation conditions. To the best of our knowledge, this is the highest (R)-AC production with high optical purity (≥98%) produced from non-food raw materials using recombinant E. coli. The supernatant of fermentation broth was mixed with diammonium phosphate (DAP) to make a total volume of 20 mL and transferred to a high-pressure microreactor. Finally, 56.72 g/L TMP was obtained in 3 h via the condensation reaction with a high conversion rate (85.30%) under optimal reaction conditions. These results demonstrated a green and sustainable approach to efficiently produce high-valued TMP, which realized value addition of low-cost renewables.